Rechtsbruch durch Verstoß gegen medienrechtliche Vorschriften - Schmitt-Mücke, Jan Heinrich (Mohr Siebeck, 2023)
Jan Heinrich Schmitt-Mückes in-depth study of the development of competition and media law examines the extent to which media law provisions are enforceable under unfair competition law. By comparing the protective purposes of both laws, he develops abstract criteria to classify media law regulations.
PublicationDate: 20231206
Keywords: Wettbewerb staatlicher und privater Medien -- Private Rechtsdurchsetzung öffentlich-rechtlicher Vorschriften -- Medienwettbewerb -- Neurowissenschaft -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht